Akuntansi Manajemen Lingkungan, Inovasi Hijau, dan Dampaknya Terhadap Kinerja Manajerial - Endang Dwi Wahyuni; Driana Leniwati; Neyla Salsabila (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: The study aims to explain how the application of environmental management accounting and green innovation affects managerial performance in manufacturing companies listed in the BEI in 2021. Methodology/approach: Research methods using explanatory methods. Of the 198 manufacturing companies sampled using purposive sampling, 60 companies obtained samples. Findings: Research results show that environmental management accounting has no impact on managerial performance, and product innovation has an impact on management performance. Environmental management accounting has no impact because some companies charge relatively small environmental costs. But in a descriptive analysis test on the mean value, it yields a minus value, which means that the accounting company's operating cash flow value in 2020 is smaller than in 2021, thus yielding a minus. Practical implications: This is because, at the time of the COVID pandemic, the results were in line with the triple bottom line theory, which measures the performance of a company in a comprehensive way by focusing on profit-making, social concerns, and environmental conservation. Originality/value: In Stakeholder Theory, companies determine and determine environmental management strategies and accounting that are able to maintain the interests of stakeholders, which later stakeholders can contribute to the company to improve company performance and value in the future. Green Innovation can also improve managerial performance by applying new technologies (hardware or software) related to production processes that will lead to energy efficiency, pollution reduction, waste recycling, environmentally friendly design and environmental management within the company.